Development of a web based decision support system for agricultural water management of small reservoirs and small water infrastructures in the Limpopo basin, CPWF Innovation Funds Project Completion Report - Alemaw, B.F.; Manzungu, Emmanuel (2013)
Small reservoirs (SRs) are important sources of water for the sustenance of rural livelihoods in the Limpopo River Basin mainly because large parts of the basin endure semi-arid conditions and unpredictable rain fall. While the exact number of small reservoirs is not known, there are indications that they are quite common. For example 256 were found in one district in Zimbabwe. The Challenge Program on Water and Food –phases 1 and 2 -have devoted considerable financial and human resources to finding ways of enhancing food and water security. Research in Mozambique, Botswana, South Africa and Zimbabwe showed that rural people depend on small reservoirs for many uses including domestic water consumption, livestock watering, brickmaking, and food production among others.